2010
DOI: 10.1093/jxb/erq130
|View full text |Cite
|
Sign up to set email alerts
|

QTL dynamics for fruit firmness and softening around an ethylene-dependent polygalacturonase gene in apple (Malusxdomestica Borkh.)

Abstract: Apple fruit are well known for their storage life, although a wide range of flesh softening occurs among cultivars. Loss of firmness is genetically coordinated by the action of several cell wall enzymes, including polygalacturonase (PG) which depolymerizes cell wall pectin. By the analysis of ‘Fuji’ (Fj) and ‘Mondial Gala’ (MG), two apple cultivars characterized by a distinctive ripening behaviour, the involvement of Md-PG1 in the fruit softening process was confirmed to be ethylene dependent by its transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
113
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(128 citation statements)
references
References 45 publications
11
113
2
2
Order By: Relevance
“…A new strategy for detecting QTLs (e.g., metaQTL analysis) could also be beneficial. Several QTLs for fruit texture and storability traits have been identified on this chromosome (Ben Sadok et al, 2015;Bink et al, 2014;Chagné et al, 2014;Costa et al, 2010;Kenis et al, 2008;King et al, 2000;Kumar et al, 2013;Kunihisa et al, 2014;Longhi et al, 2013b). Our findings confirm the importance of chr 10 for elucidating the regulatory mechanisms of fruit texture and storability.…”
Section: Other Qtlssupporting
confidence: 82%
See 3 more Smart Citations
“…A new strategy for detecting QTLs (e.g., metaQTL analysis) could also be beneficial. Several QTLs for fruit texture and storability traits have been identified on this chromosome (Ben Sadok et al, 2015;Bink et al, 2014;Chagné et al, 2014;Costa et al, 2010;Kenis et al, 2008;King et al, 2000;Kumar et al, 2013;Kunihisa et al, 2014;Longhi et al, 2013b). Our findings confirm the importance of chr 10 for elucidating the regulatory mechanisms of fruit texture and storability.…”
Section: Other Qtlssupporting
confidence: 82%
“…The relationships between harvest time, ADM, and genotypes of Md-PG1 SSR 10kd were of interest because QTLs for harvest time and storability traits have been identified in the flanking region of MdPG1 Costa et al, 2010;Kenis et al, 2008;Kunihisa et al, 2014). Weak correlations observed between harvest time and ADM values for the OA (r = −0.39, P < 0.001) and accessions (r = −0.37, P < 0.001) were consistent with the weak negative correlation between harvest time and storability found in a bi-parental population and genetic resources (Nybom et al, 2013).…”
Section: Relationship Between Harvest Time Adm and Genotypes Of Md-pmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the tomato and apple are both climacteric fruit, we first used the heterologous gene expression profiles in tomato fruit development as clues. Costa et al (2010) identified 652 genes differentially expressed during tomato fruit development, and we used these sequences as queries to perform a BLASTN search against all the RING-containing genes in apple. Interestingly, only two putative clusters, SGN-U213593 and SGN-U212955, exhibited similarity with one apple RING-H2 type protein, MDP0000303817, indicating the rarity of differentially expressed RING-containing E3 proteins in apple.…”
Section: Ring Finger Proteins and Fruit Developmentmentioning
confidence: 99%